All in a game - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Kodja Agnigbangniweke, the manager of GAVAB in Lomé, Togo, thinks that Spore should feature games for readers. 'To make Spore more interesting and exciting, I'd like to suggest that you run quiz competitions, with questions covering agriculture....